2006
DOI: 10.1590/s1413-35552006000100007
|View full text |Cite
|
Sign up to set email alerts
|

Análise da resposta da freqüência cardíaca durante a realização de exercício isocinético excêntrico de grupamento extensor de joelho

Abstract: Objetivo: Investigar a magnitude da resposta da freqüência cardíaca durante o exercício isocinético excêntrico do grupamento extensor do joelho, em diferentes velocidades angulares. Materiais e Métodos: Dez voluntários jovens, sadios e ativos foram submetidos a contração excêntrica máxima do grupo extensor do joelho dominante. Foi utilizado um dinamômetro isocinético, nas velocidades de 30 o /s, 60 o /s e 120 o /s, ordenadas aleatoriamente. A FC foi obtida batimento a batimento, na derivação eletrocardiográfic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
0
3
0
2
Order By: Relevance
“…During the maximal efforts trials, they were motivated with visual feedback and consistent verbal encouragement. In addition, the subjects were oriented to avoid the Valsalva's maneuver and to breathe spontaneously (i.e., to not hold their breath during the effort) 20 . The mean of the maximum torque (Nm) of the all repetitions was calculated and a unique value for each test was determined by the sum of the mean of the extension and flexion contraction.…”
Section: Isokinetic Torquementioning
confidence: 99%
See 1 more Smart Citation
“…During the maximal efforts trials, they were motivated with visual feedback and consistent verbal encouragement. In addition, the subjects were oriented to avoid the Valsalva's maneuver and to breathe spontaneously (i.e., to not hold their breath during the effort) 20 . The mean of the maximum torque (Nm) of the all repetitions was calculated and a unique value for each test was determined by the sum of the mean of the extension and flexion contraction.…”
Section: Isokinetic Torquementioning
confidence: 99%
“…The literature reports that torque magnitude is also influenced by angular velocity, since during concentric exercise, a decrease in maximum voluntary torque is observed as consequence of higher angle acceleration for young 2,[6][7][8][14][15][16][17] and older subjects 18 . On the other hand, there are conflicting results about angular velocity during eccentric action as different studies have found that torque development during eccentric actions remains similar 2 or increases from slow to fast angular velocities 5,19,20 . Concerning the influences of angular velocity on electromyography (EMG) signals, there are conflicting results in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Tem sido observado aumento no volume de treinamento após utilização de IR de três minutos quando comparado a um minuto 33,34 . Já Malfatti et al 35 sugerem que para a manutenção do volume de trabalho durante uma sessão de reabilitação da força muscular em idosos, os IR's não só devem ser superiores a 60 segundos, como também aumentados à medida que as séries subsequentes são realizadas.…”
Section: Discussionunclassified
“…Body mass and height (9) were checked for determining the Body Mass Index (BMI) (10), blood pressure (11) and heart rate were also verified (12).…”
Section: Methodsmentioning
confidence: 99%